Antimicrobial Ionic Liquids with Fumarate Anion - Biyan He; Guangnan Ou; Changyi Zhou; Meihong Wang; Suyan Chen (Journal of Chemistry)
The shortage of new antimicrobial drugs and increasing resistance of microbe to antimicrobial agents have been of some concern. The formulation studies of new antibacterial and antifungal agents have been an active research field. Ionic liquids are known as designed liquids with controllable physical/chemical/biological properties and specific functions, which have been attracting considerable interest over recent years. However, no attention has been made towards the preparation of ionic liquids with antimicrobial activities. In this paper, a new class of ionic liquids (ILs) with fumarate anion was synthesized by neutralization of aqueous 1-butyl-3-methylimidazolium hydroxide with equimolar monoester fumarate and characterized using NMR and thermal gravimetric analysis. The ILs are soluble in water and polar organic solvents and also soluble in the common ILs. The antimicrobial activities of the ILs are more active than commercially available potassium sorbate and are greatly affected by the alkyl chain length. The significant antimicrobial properties observed in this research suggest that the ILs may have potential applications in the modern biotechnology.